Determination of cefuroxime lysine in rat brain microdialysates by ultra‐fast liquid chromatography with UV and tandem mass spectrometry: application to an acute toxicokinetic study. (11th February 2014) - Zhao, Longshan; Li, Qing; Zhu, Heyun; Chen, Xiaohui; Bi, Kaishun
ABSTRACT Cefuroxime lysine is a new second‐generation cephalosporins, which can penetrate the blood–brain barrier to cure the meningitis. In order to investigate its acute toxicokinetic study after intraperitoneal injection of 675 mg/kg cefuroxime lysine, a sensitive and clean ultra‐fast liquid chromatography–tandem mass spectrometry (UFLC‐MS/MS) method for the determination of cefuroxime lysine in microdialysate samples was developed and validated, which was compared with UFLC‐UV as a reference method. Chromatographic separation was performed on a Shim‐pack XR‐ODS C18 column (75 × 3.0 mm, 2.2 µm), with an isocratic elution of 0.1% formic acid in acetonitrile–0.1% formic acid in water (45:55, v/v) for LC‐MS and acetonitrile–20 mm potassium dihydrogen phosphate (pH 3.0, 20:80, v/v) for LC‐UV. The lower limit of detection was 0.01 µg/mL for LC‐MS and 0.1 µg/mL for LC‐UV method, with the same corresponding linearity range of 0.1–50 µg/mL. The intra‐ and inter‐day precisions (relative standard deviation) for both methods were from 1.1 to 8.9%, while the accuracy was all within ±10.9%. The results of both methods were finally compared using paired t‐test; the results indicated that the concentrations measured by the two methods correlated significantly (p < 0.05), which suggested that the two methods based on LC‐MS and LC‐UV were suitable for the acute toxicokinetic study. Copyright © 2014 John Wiley & Sons, Ltd.